PREVALENCE AND PREDICTORS OF UNCIRCUMCISED, KENYAN MEN’S DESIRE FOR CIRCUMCISION FOR THEIR INFANT SONS - Hudson, F. Parker (AIDS Behav, 2018)
Men are key decision makers for their son’s circumcision, so understanding their attitudes and beliefs is important for assessing uptake of early infant male circumcision in countries in sub-Saharan Africa that have high HIV prevalence. We analyzed men’s preferences for circumcising their sons using data from a population-representative survey of 1,501 uncircumcised Kenyan men aged 25–49 years. Most men (59%) reported they would “definitely” want their son circumcised when asked about a hypothetical scenario of having a son born in the year of the survey. However, only 25% reported a similar desire to become circumcised themselves. In multivariable Poisson regression models to estimate prevalence ratios, key predictors of the desire to circumcise their sons included knowledge that circumcision reduces HIV acquisition, having a supportive partner, discussing circumcision with the partner, altruism, and intention of the man to be circumcised himself. Focusing on the above partner dynamics likely has the greatest capacity to increase demand, since 55% had not talked to their partner about circumcision.